Cidades de fogo e paixão/Cities of fire and passion - Wenceslao Machado de Oliveira Júnior (Universidade Estadual de Campinas, 2007)
Estudo sobre o cinema, e a criação do real urbano no cinema, através do espaço e do tempo cinemográficos no filme Fogo e Paixão, de Isay Weinfeld e Marcio Kogan. Study about motion picture, and the creation of the real urban in the movies, through space and cinemographic times in the film Fire and Passion, of Isay Weinfeld and Marcio Kogan.